Mica paper treating fluid for new energy ships, waterproof salt-fog-resistant anti-aging mica plate and preparation method of mica plate
Through the specific composition of mica paper treatment liquid and coating technology, anti-aging mica boards with excellent insulation, waterproof and salt spray resistance were prepared, which solved the problem of mica cover plate aging in the sea environment of the new energy ship power battery, and improved the Safety and durability.
Patent Information
- Application Number
- CN202411400540.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2024-12-31
AI Technical Summary
The mica cover plate in the power battery of the new energy ship has aging in the sea environment, causing insulation failure, causing safety hazards, and the prior art is difficult to effectively improve its aging resistance.
A specific composition of mica paper treatment solution, including high temperature resistant silicone, sodium methyl silicate and silane coupling agent, is used as treatment solution A, combined with epoxy resin, acrylic resin and silicon carbide ceramic as treatment solution B, and is coated with glue and Seamless coating technology to prepare waterproof, salt spray-resistant and anti-aging mica boards.
It significantly improves the insulation performance, waterproof and salt spray resistance of mica boards, extends its service life, avoids bubbles, layering, pores, embrittlement and other adverse phenomena that occur during aging, and improves safety.
Smart Images

Figure BDA0005075155310000051 
Figure BDA0005075155310000061 
Figure BDA0005075155310000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of mica materials, and in particular to a mica paper treatment liquid for new energy ships, a waterproof, salt spray, and anti-aging mica board, and a preparation method thereof. Background Art
[0002] At present, the shipbuilding industry is a microcosm of modern large-scale industry. The shipbuilding industry is not only an equipment industry for water transportation, energy transportation, marine development and other industries, but also an important part of the national defense industry, which determines its important position in the national economy. Historically, both advanced industrial countries and backward industrial countries have developed the shipbuilding industry as a key industry in the process of industrialization in their countries, and have played an important role. The shipbuilding industry was highly valued by the most developed countries at that time, and was given priority development as a leading industry. It became one of the symbols of the developed economy and strong national strength of these countries, and was identified as a strategic industry closely related to national economic security. Since electric ships are subject to battery life, charging speed and distribution of charging facilities, for some long-distance voyages and large-scale transportation of goods along the coast and ocean, electric ships are difficult to meet the actual needs, but in the inland shipping of medium and short-distance transportation and small and medium-sized transportation, electric ships have a bright future, so the increase in the output of electric ships will become an industry trend in the future.
[0003] With the gradual improvement of my country's power battery technology, breakthroughs have been made from battery cell materials to space utilization, the endurance of power batteries has been greatly improved, and safety has received further attention. Compared with new energy vehicles, new energy ships are more affected by the environment, especially the sea breeze and seawater corrosion. In particular, the internal thermal runaway protection of the battery pack as the power system. When the environmental aging causes the insulation failure, serious accidents will occur. Therefore, improving the aging resistance of the mica cover plate in the power battery is an important issue for the safe sailing of new energy ships. Summary of the invention
[0004] In order to solve the above technical problems, the present application provides a new energy ship mica paper treatment liquid, a waterproof, salt spray, and anti-aging mica board, and a preparation method thereof.
[0005] In a first aspect, the present application provides a mica paper processing liquid, including a processing liquid A and a processing liquid B; The treatment liquid A comprises the following components in parts by weight: 40-50 parts of high temperature resistant organic silica gel, 25-35 parts of sodium methyl silicate, and 4-6 parts of silane coupling agent; The treatment liquid B comprises the following components in parts by weight: 30-40 parts of epoxy resin, 10-20 parts of acrylic resin, 6-8 parts of silicon carbide ceramics, and 0.5-1 part of coupling agent.
[0006] Mica has good high temperature resistance and insulation. The high temperature resistant organic silica gel in the treatment liquid A has a very flexible main chain, and its intermolecular force is weak, providing suitable viscosity, weak surface tension, small surface energy, and strong film-forming ability, so that the surface structure of the mica board after molding is good. Sodium methyl silicate has good permeability and crystallinity. The silanol groups in its molecular structure react with the silanol groups in the silicate material to dehydrate and cross-link, thereby realizing the "reverse capillary effect" to form an excellent hydrophobic layer, and at the same time has the function of micro-expansion and increasing density. The coupling agent provides excellent bonding force, which makes the mica material have good waterproof performance.
[0007] In treatment liquid B, epoxy resin and acrylic resin cooperate with each other to provide excellent corrosion resistance. Silicon carbide ceramics can fill the pores between the fine particles of treatment liquid B, and cooperate with other substances in treatment liquid B to increase the viscosity and toughness of the system, while improving the corrosion resistance and aging resistance of the mica board.
[0008] Preferably, the mica paper treatment liquid includes treatment liquid A and treatment liquid B; The treatment liquid A comprises the following components in parts by weight: 43-48 parts of high temperature resistant organic silica gel, 28-33 parts of sodium methyl silicate, and 4.5-5.5 parts of silane coupling agent; The treatment liquid B comprises the following components in parts by weight: 32-37 parts of epoxy resin, 13-18 parts of acrylic resin, 6.5-7.5 parts of silicon carbide ceramics, and 0.6-0.8 parts of coupling agent.
[0009] Preferably, in the treatment liquid A, the high temperature resistant organic silica gel is selected from one or more of SH-9501, SH-9602, and SH-5202S; the silane coupling agent is selected from any one or more of vinyl silane coupling agent, amino silane coupling agent, and methacryloxy silane coupling agent.
[0010] Preferably, in the treatment liquid B, the coupling agent is selected from one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, propyltriethoxysilane, ethylenediaminepropyltriethoxysilane, ethylenediaminepropylmethyldimethoxysilane, vinyltriacetoxysilane and vinyltriethoxysilane.
[0011] Preferably, the treatment liquid A is prepared by weighing the corresponding weights of the raw material components respectively, stirring for ≥60 min under the condition of a stirring speed ≥500 rpm to prepare the treatment liquid A.
[0012] During the test of the preparation method of the treatment liquid A, the applicant found that when the stirring speed was lower than 500 rpm, the uniformity was poor; when the stirring time was lower than 60 min, the uniformity was poor. Therefore, the present application controls the parameters within the above range.
[0013] Preferably, the preparation method of the treatment liquid B is: weigh the corresponding weights of the raw material components respectively, put them into a reaction kettle, and stir for ≥30 min at a temperature of 90-110° C. and a stirring speed of ≥80 rpm to prepare the treatment liquid B.
[0014] During the test of the preparation method of treatment liquid B, the applicant found that when the temperature of the reactor was lower than 90°C, the film-forming effect was poor; when the temperature of the reactor was higher than 110°C, solidified products appeared in the mixed liquid; when the stirring speed was lower than 80rpm, the mixing was uneven and the coating was uneven; when the stirring time was lower than 30min, the mixing was uneven and the coating was uneven. Therefore, the present application controls the parameters within the above range.
[0015] Furthermore, the temperature of the reactor is 95-105°C.
[0016] During the test of the preparation method of the treatment liquid B, the applicant found that when the temperature of the reactor is controlled at 95-105°C, the waterproof performance of the mica board can be further improved.
[0017] In a second aspect, the present application provides a waterproof, salt-fog-resistant, and anti-aging mica board, which is prepared by impregnating phlogopite mica paper with the above-mentioned mica paper treatment solution.
[0018] In a third aspect, the present application provides a method for preparing the above-mentioned waterproof, salt fog, and anti-aging mica board, which specifically comprises the following steps: The treatment liquid A is evenly coated on the surface of the phlogopite mica paper by a coating method, and the coating speed is 0.2-0.4L / min. After the mica paper is coated, a mica board is produced by a mica board hot press to obtain a pretreated mica board; the parameters of the hot pressing are: the hot pressing temperature is 170-210°C, the pressure is 1.8-2.2Mpa, and the hot pressing time is ≥30min; The treatment liquid B is coated on the surface of the pretreated mica board by a gap coating method, the gap of the gap is 0.05±0.02mm, and then the waterproof, salt spray, anti-aging mica board is obtained by drying; the drying parameter conditions are: divided into three zones for drying, each zone is 7-9m long, the vehicle speed during drying is 3-6m / min, the temperature of zone one is 50-60℃, the temperature of zone two is 100-120℃, and the temperature of zone three is 130-150℃.
[0019] During the test of the preparation method of waterproof, salt spray and aging resistant mica board, the applicant found that when the coating speed is lower than 0.2L / min, the protective layer cannot be formed evenly and the resistance to salt spray aging is poor; when the laminating machine speed is higher than 0.4m / s, the mica paper is easily dislocated and torn during hot pressing. When the hot pressing temperature is greater than 200°C, the waterproof layer of the mica board is damaged, affecting the waterproof effect; when the hot pressing temperature is lower than 160°C, the mica board is not completely cured and stratification occurs between layers. When the pressure is higher than 2.2Mpa, the mica board is deformed; when the pressure is lower than 1.8Mpa, the adhesion between the mica layers is poor. When the hot pressing time is lower than 20min, the adhesion between the mica layers is poor.
[0020] During the test of the preparation method of waterproof, salt-fog-resistant and anti-aging mica board, the applicant found that if the gap between the slits is greater than 0.07mm, cracks are likely to appear after drying; if the gap between the slits is less than 0.03mm, the anti-salt-fog effect is poor. The vehicle speed during drying is 3-6m / min. When the vehicle speed is lower than 3m / min, the coating cannot be cured. When the vehicle speed is higher than 6m / min, bubbles appear on the coating surface. When the temperature of the first drying zone is lower than 50°C, the solvent in the glue cannot be dried in the first zone. When the temperature of the first zone is higher than 60°C, bubbles appear on the surface. When the temperature of the second zone is lower than 100°C, the coating liquid cannot be cured. When the temperature of the second zone is higher than 120°C, bubbles appear on the surface. When the temperature of the third zone is lower than 130°C, the surface is anti-sticky. When the temperature of the third zone is higher than 150°C, cracks appear.
[0021] Preferably, the hot pressing parameters are as follows: hot pressing temperature is 180-200° C., pressure is 1.9-2.1 MPa, and hot pressing time is 40-60 min.
[0022] During the test of the method for preparing waterproof, salt spray and anti-aging mica boards, the applicant found that when the hot pressing temperature was 160-170°C or 190-200°C, the water absorption of the mica board after the aging test was large. When the pressure was 1.8-1.9Mpa or 2.1-2.2Mpa, the water absorption of the mica board after the aging test was large. Therefore, the present application controls the hot pressing temperature and pressure parameters within the above range.
[0023] Preferably, the drying parameters are as follows: divided into three zones for drying, each zone being 7.5-8.5 m long, the vehicle speed being 4-5 m / min, the temperature of zone one being 53-58°C, the temperature of zone two being 105-115°C, and the temperature of zone three being 135-145°C.
[0024] During the test of the preparation method of waterproof, salt spray and aging resistant mica board, the applicant found that when the length of each zone was controlled to be 7.5-8.5m, the vehicle speed during drying was 4-5m / min, the temperature of zone 1 was 53-58°C, the temperature of zone 2 was 105-115°C, and the temperature of zone 3 was 135-145°C, the water absorption of the mica board after the aging test was small, that is, the temperature of each drying zone was controlled within the above range in the present application, which further improved the aging resistance of the mica board.
[0025] In summary, the technical solution of this application has the following effects: The present application uses specific weight portions of high temperature resistant organic silica gel, sodium methyl silicate and silane coupling agent as raw material components of treatment liquid A, and specific weight portions of epoxy resin, acrylic resin, silicon carbide ceramic and coupling agent as raw material components of treatment liquid B. Treatment liquid A is evenly coated on the surface of phlogopite mica paper by a coating method, and then a press is used to produce mica boards. Then, a salt spray resistant coating (treatment liquid B) is coated on the surface of the mica board by a gap coating method, and the coating is prepared by drying. The prepared waterproof, salt spray resistant and aging resistant mica board has good insulation performance, excellent waterproof and salt spray resistance, and thus excellent aging resistance.
[0026] The method for preparing the waterproof, salt spray, resistant and aging-resistant mica board provided in the present application is simple to operate and reduces production costs. By controlling the types and amounts of raw materials and the specific process parameters during the preparation method, the occurrence of bubbles, stratification, pores, embrittlement, cracks, powder loss, unevenness, orange peel and other undesirable phenomena during the forming process of the waterproof, salt spray, resistant and aging-resistant mica board is avoided.
[0027] The present application further improves the aging resistance of the waterproof, salt spray and aging resistant mica board by screening the type of high temperature resistant organic silica gel in the treatment liquid A and the type of coupling agent in the treatment liquid B. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a process flow chart of the method for preparing the waterproof, salt spray, and anti-aging mica board in the embodiment of the present application. DETAILED DESCRIPTION
[0029] The present application is further described in detail below in conjunction with examples, comparative examples and performance testing experiments. These examples should not be construed as limiting the scope of protection claimed in the present application. Example
[0030] Examples 1-15 Embodiments 1-15 respectively provide a waterproof, salt-fog-resistant, and anti-aging mica board and a preparation method thereof.
[0031] The difference between the above embodiments is that the amounts of the components in the treatment liquid A and the treatment liquid B are different, as shown in Table 1.
[0032] The process flow chart of the preparation method of the waterproof, salt spray, and anti-aging mica board in the above embodiment is as follows: Figure 1 As shown, the specific steps are: The preparation method of treatment liquid A is as follows: according to Table 1, the corresponding weights of the raw material components of high-temperature resistant organic silica gel (composed of a mixture of SH-9501 and SH-5202S in a weight ratio of 3:1), sodium methyl silicate, and aminosilane coupling agent are respectively weighed, and stirred for 80 minutes at a stirring speed of 600 rpm to prepare a mica paper treatment liquid.
[0033] The preparation method of treatment liquid B is as follows: according to Table 1, the corresponding weights of the raw material components epoxy resin, acrylic resin, silicon carbide ceramic (from Hangzhou Jikang New Materials Co., Ltd., specification SiC2000), and coupling agent (composed of a mixture of propyltriethoxysilane and vinyltriacetoxysilane in a weight ratio of 10:1) are weighed respectively, put into a reaction kettle, and stirred for 40 minutes at a temperature of 60°C and a stirring speed of 100 rpm to prepare treatment liquid B.
[0034] The treatment liquid A was evenly coated on the surface of phlogopite paper (the model of mica paper was P506, purchased from Pingjiang County Weipai Mica Insulation Material Co., Ltd.) by coating at a speed of 0.3 L / min. A press was used for hot pressing to obtain a pretreated mica board. The parameters of the hot pressing were: hot pressing temperature of 190°C, pressure of 2.0 MPa, and hot pressing time of 50 min.
[0035] The treatment liquid B is coated on the surface of the pretreated mica board by means of gap coating, and then dried to obtain a waterproof, salt spray, anti-aging mica board with a gap of 0.05 mm. The drying parameters are as follows: divided into three zones for drying, each zone is 8 m long, the vehicle speed is 4.5 m / min during drying, the temperature of zone 1 is 55°C, the temperature of zone 2 is 110°C, and the temperature of zone 3 is 140°C.
[0036] Table 1 Amount of each component in the treatment solution A and the treatment solution B in Examples 1-15 Examples 16-19 Examples 16-19 respectively provide a waterproof, salt-fog-resistant, and anti-aging mica board and a preparation method thereof.
[0037] The difference between the above embodiment and embodiment 1 is that the type of high temperature resistant organic silica gel in the treatment liquid A is different, as shown below.
[0038] In Example 16: the high temperature resistant organic silica gel is composed of a mixture of SH-9501 and SH-9602 in a weight ratio of 3:1.
[0039] In Example 17: the high temperature resistant organic silica gel is composed of a mixture of SH-9501 and SH-5202S in a weight ratio of 1:3.
[0040] In Example 18: the high temperature resistant organic silica gel is composed of a mixture of SH-9501 and SH-5202S in a weight ratio of 3:0.5.
[0041] In Example 19: the high temperature resistant organic silica gel is composed of a mixture of SH-9501 and SH-5202S in a weight ratio of 3:1.5.
[0042] The other raw materials and the preparation method of the mica board in the above embodiment are the same as those in embodiment 1.
[0043] Examples 20-23 Examples 20-23 respectively provide a waterproof, salt spray, and anti-aging mica board and a preparation method thereof.
[0044] The difference between the above embodiment and embodiment 1 is that the type of coupling agent in the treatment liquid B is different, as shown below.
[0045] In Example 20: the coupling agent is composed of a mixture of propyltriethoxysilane and ethylenediaminepropyltriethoxysilane in a weight ratio of 10:1.
[0046] In Example 21: the coupling agent is composed of a mixture of propyltriethoxysilane and vinyltriacetoxysilane in a weight ratio of 1:10.
[0047] In Example 22: the coupling agent is composed of a mixture of propyltriethoxysilane and vinyltriacetoxysilane in a weight ratio of 10:0.5.
[0048] In Example 23: the coupling agent is composed of a mixture of propyltriethoxysilane and vinyltriacetoxysilane in a weight ratio of 10:1.5.
[0049] The other raw materials and the preparation method of the mica board in the above embodiment are the same as those in embodiment 1.
[0050] Comparative Example Comparative Examples 1-14 Comparative Examples 1-14 respectively provide a mica board and a preparation method thereof.
[0051] The difference between the comparative example and Example 1 is that the amounts of the components in the treatment liquid A and the treatment liquid B are different, as shown in Table 2.
[0052] Table 2 Amount of each component in the treatment solution A and the treatment solution B in Comparative Examples 1-14 The types of raw materials and the preparation method of the mica board in the above comparative example are the same as those in Example 1.
[0053] Comparative Examples 15-17 Comparative Examples 15-17 respectively provide a mica board and a preparation method thereof.
[0054] The differences between the above comparative example and Example 1 are specifically as follows.
[0055] In Comparative Example 15: In the treatment solution A, an equal amount of sodium ethyl silicate was used instead of sodium methyl silicate.
[0056] In Comparative Example 16: In the treatment solution B, an equal amount of phenolic epoxy resin was used instead of acrylic resin.
[0057] In Comparative Example 17: an equal amount of aluminum hydroxide was used to replace silicon carbide ceramic.
[0058] The other raw materials and the preparation method of the mica board in the above comparative example are the same as those in Example 1.
[0059] Performance testing (1) Surface properties: Observe whether there are defects on the surface of the mica board during the preparation process and on the surface of the prepared mica board product.
[0060] (2) Insulation: Refer to the national standard GB / T5019.2-2009 test method and use a voltage withstand tester to test the voltage withstand performance of the mica board.
[0061] (3) Waterproof performance: Soak the mica board in water for 60 minutes, take out the absorbent paper and gently wipe it dry, and use an electronic balance to test the water absorption performance of the mica board.
[0062] (4) Salt spray resistance: The test was conducted using a salt spray test machine for 1000 hours to test the salt spray resistance.
[0063] (5) Aging resistance: The mica board was exposed to a double-lamp closed carbon arc for 720 hours to test its voltage resistance and waterproof performance.
[0064] Test results: as shown in Table 3.
[0065] Table 3 Performance test results of mica boards in Examples 1-23 and Comparative Examples 1-17 It was found through experiments that the mica board surface prepared by the technical solution of the present application was intact and free of defects during the preparation process, and after the aging test, the mica board sample was still intact and free of defects.
[0066] When the high temperature resistant organic silica gel in the treatment liquid A in Comparative Example 1 was less than 40 parts by weight, the mica board layers were delaminated (the mica board was formed by laminating multiple layers of mica paper).
[0067] When the high temperature resistant organic silica gel in the treatment liquid A in Comparative Example 2 was higher than 50 parts by weight, bubbles appeared on the surface of the mica board.
[0068] When the proportion of sodium methyl silicate in the treatment solution A in Comparative Example 3 is less than 25 parts by weight, the water absorption rate of the mica board is greater than 1%, and it is easy to absorb moisture.
[0069] When the sodium methyl silicate in the treatment solution A in Comparative Example 4 was higher than 35 parts by weight, cracks appeared on the mica board.
[0070] When the silane coupling agent in the treatment liquid A in Comparative Example 5 was less than 4 parts by weight, the mica board was delaminated after curing.
[0071] When the amount of treatment liquid A in Comparative Example 6 was higher than 6 parts by weight, bubbles appeared on the surface of the mica board after curing.
[0072] When the epoxy resin in the treatment liquid B of Comparative Example 7 is less than 30 parts by weight, the anti-salt spray corrosion effect is poor.
[0073] When the epoxy resin in the treatment liquid B of Comparative Example 8 was higher than 40 parts by weight, bubbles appeared on the surface coating of the mica board.
[0074] When the acrylic resin in the treatment liquid B in Comparative Example 9 is less than 10 parts by weight, the film-forming property of the anti-salt spray coating is poor.
[0075] When the acrylic resin in the treatment liquid B in Comparative Example 10 was higher than 20 parts by weight, the surface of the mica board was sticky and a film could not be formed.
[0076] When the silicon carbide ceramic in the treatment liquid B in Comparative Example 11 is less than 6 parts by weight, the coating has poor wear resistance.
[0077] When the silicon carbide ceramic in the treatment solution B in Comparative Example 12 was higher than 8 parts by weight, the coating surface was uneven and had an orange peel appearance.
[0078] When the coupling agent in the treatment liquid B in Comparative Example 13 was less than 0.5 parts by weight, bubbles appeared in the mixed liquid.
[0079] When the coupling agent in the treatment solution B in Comparative Example 14 was higher than 1 part by weight, white powder appeared on the coating surface.
[0080] Combined with Table 2, by comparing the test results of Examples 1-23 with those of Comparative Examples 1-19, it can be seen that the present application uses specific weight portions of high temperature resistant organic silica gel, sodium methyl silicate, and silane coupling agent as raw material components of treatment liquid A, and specific weight portions of epoxy resin, acrylic resin, silicon carbide ceramic, and coupling agent as raw material components of treatment liquid B, and the treatment liquid A is evenly coated on the surface of phlogopite paper by a coating method, and then a press is used to produce mica boards, and then the salt spray resistant coating (treatment liquid B) is coated on the surface of the mica board by a gap coating method, and the coating is prepared by drying. The prepared waterproof, salt spray resistant, and aging-resistant mica board has excellent apparent properties, good insulation performance, excellent waterproof and salt spray resistance, and thus excellent aging resistance.
[0081] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A mica paper treatment liquid, characterized in that: including a treatment liquid A and a treatment liquid B; The treatment liquid A comprises the following components in parts by weight: 40-50 parts of high temperature resistant organic silica gel, 25-35 parts of sodium methyl silicate, and 4-6 parts of silane coupling agent; The treatment liquid B comprises the following components in parts by weight: 30-40 parts of epoxy resin, 10-20 parts of acrylic resin, 6-8 parts of silicon carbide ceramics, and 0.5-1 part of coupling agent.
2. The mica paper treating liquid according to claim 1, characterized in that: including a treatment liquid A and a treatment liquid B; The treatment liquid A comprises the following components in parts by weight: 43-48 parts of high temperature resistant organic silica gel, 28-33 parts of sodium methyl silicate, and 4.5-5.5 parts of silane coupling agent; The treatment liquid B comprises the following components in parts by weight: 32-37 parts of epoxy resin, 13-18 parts of acrylic resin, 6.5-7.5 parts of silicon carbide ceramics, and 0.6-0.8 parts of coupling agent.
3. The mica paper treating liquid according to claim 1, characterized in that: In the treatment liquid A, the high temperature resistant organic silica gel is composed of a mixture of SH-9501 and SH-5202S in a weight ratio of 3:0.5-1.5; the silane coupling agent is selected from any one or more of vinyl silane coupling agent, amino silane coupling agent, and methacryloxy silane coupling agent.
4. The mica paper treating liquid according to claim 1, characterized in that: In the treatment liquid B, the coupling agent is composed of a mixture of propyltriethoxysilane and vinyltriacetoxysilane in a weight ratio of 10:0.5-1.
5.
5. The mica paper treating liquid according to claim 1, characterized in that: The preparation method of the treatment liquid A is as follows: weigh the corresponding weights of the raw material components respectively, stir for ≥60 min at a stirring speed of ≥500 rpm, and prepare the treatment liquid A; the preparation method of the treatment liquid B is as follows: weigh the corresponding weights of the raw material components respectively, put them into a reaction kettle, stir for ≥30 min at a temperature of 90-110°C and a stirring speed of ≥80 rpm, and prepare the treatment liquid B.
6. A waterproof, salt-fog-resistant, and anti-aging mica board, characterized in that: The phlogopite paper is prepared by subjecting the phlogopite paper to a gum-impregnation treatment using the mica paper treatment solution described in any one of claims 1 to 5.
7. The method for preparing the waterproof, salt-fog-resistant and anti-aging mica board according to claim 6, characterized in that: The specific steps include: The treatment liquid A is evenly coated on the surface of the phlogopite mica paper by a coating method, and the coating speed is 0.2-0.4L / min. After the mica paper is coated, a mica board is produced by a mica board hot press to obtain a pretreated mica board; the parameters of the hot pressing are: the hot pressing temperature is 170-210°C, the pressure is 1.8-2.2Mpa, and the hot pressing time is ≥30min; The treatment liquid B is coated on the surface of the pretreated mica board by a gap coating method, the gap of the gap is 0.05±0.02mm, and then the waterproof, salt spray, anti-aging mica board is obtained by drying; the drying parameter conditions are: divided into three zones for drying, each zone is 7-9m long, the vehicle speed during drying is 3-6m / min, the temperature of zone one is 50-60℃, the temperature of zone two is 100-120℃, and the temperature of zone three is 130-150℃.
8. The method for preparing the waterproof, salt-fog-resistant and aging-resistant mica board according to claim 7, characterized in that: The parameters of the hot pressing are as follows: the hot pressing temperature is 180-200° C., the pressure is 1.9-2.1 MPa, and the hot pressing time is 40-60 min.
9. The method for preparing the waterproof, salt fog resistant and aging resistant mica board according to claim 7, characterized in that: The drying parameters are as follows: divided into three zones for drying, each zone being 7.5-8.5 m long, the vehicle speed being 4-5 m / min, the temperature of zone 1 being 53-58°C, the temperature of zone 2 being 105-115°C, and the temperature of zone 3 being 135-145°C.
10. Application of the waterproof, salt-fog-resistant and anti-aging mica sheet according to claim 6 in mica sheets for connectors of new energy ship power systems.
Citation Information
Patent Citations
Hydrophobic polymer cement waterproof coating and preparation method thereof
CN105272047A
High-pressure-resistant reverse needle valve
CN111594648A
New energy automobile waterproof mica plate and preparation method thereof
CN117153504A
